2015
DOI: 10.1515/rjdnmd-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Protective Effects of Quince (Cydonia Oblonga) Leaf Extract on Fertility Alterations and Gonadal Dysfunction Induced by Monosodium Glutamate in Adult Male Wistar Rats

Abstract: Background and Aims: Starting from the cytotoxic effects of monosodium glutamate (MSG), the aim of this study was to evaluate the protective effects of quince leaf extract as natural antioxidant on the reproductive dysfunction induced by monosodium glutamate in rats. Material and methods: Monosodium glutamate was administrated with a dose of 30 and 60 mg/kg and quince leaf extract was administrated with a dose of 500 mg/kg. At the end of study, body and testicular weight measurement, hormonal and epididymal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
2
4
0
4
Order By: Relevance
“…The administration of monosodium glutamate leads to increase of body weight (Diniz et al, 2005). According to our previous study, the higher dose of MSG led to more weight gain in comparison to lower doses of monosodium glutamate (Kianifard et al, 2015). The results of the present study are in consistent with previously reported results.…”
Section: Sperm Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The administration of monosodium glutamate leads to increase of body weight (Diniz et al, 2005). According to our previous study, the higher dose of MSG led to more weight gain in comparison to lower doses of monosodium glutamate (Kianifard et al, 2015). The results of the present study are in consistent with previously reported results.…”
Section: Sperm Analysissupporting
confidence: 93%
“…The weight of testes depends on the mass of differentiated spermatogenic cells (Katoh et al, 2002). The results from this study confirms our previous studies (Kianifard et al, 2013;Kianifard et al, 2015) about the effects of methylphenidate and monosodium glutamate on testicular weight loss especially when these agents both taken together. Previous studies have shown that, the MPH can alter the brain-pituitary-testicular axis (Adriani et al, 2006).…”
Section: Sperm Analysissupporting
confidence: 88%
“…HPA disruption may reduce levels of sex hormones, including testosterone, follicle-stimulating hormone, and luteinizing hormone. This ultimately leads to alterations in sperm quality [21]. Spermatogenesis is totally dependent on the sex hormones and androgen-dependent organs of the reproductive system, which include the prostate gland, epididymis and seminal vesicles.…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Other studies, however, observed improved testicular histopathology after the administration of selenium, vitamin E, and curcumin, respectively [7,22]. Treatments such as graviola extract, vitamin C, vitamin E, camel milk, propolis, quince extract, and curcumin have proven to provide protective effects against MSG-induced histomorphological testicular toxicities [17][18][19][20][21][22].…”
Section: Histomorphological Alterationsmentioning
confidence: 99%
See 1 more Smart Citation